(untitled) (European Bison Conservation Newsletter, 2013)
Habitat selection of the European bison has until now mainly been studied in the Carpathian Mountains and in the Polish and Belarusian Bialowieska Forest, where the bison selected deciduous forest-dominated habitats with a preference for complex mosaics of forest and patches of grass in the vegetative season. In May 2012, the Danish Nature Agency Bornholm introduced seven European bison to an enclosure in Almindingen Forest with the aim of creating a more open and natural forest. We examined habitat selection of two of the bison, a male and a female, which were both radio-collared, and used population extrapolation to investigate the potential of the herd as ecosystem engineers. We found that the two bison in the vegetative season spent most of their time in coniferous (45%), uncultured cut coniferous (25%) and deciduous habitat (24%). Compared with the habitat availability in the enclosure, the two bison preferred uncultured cut coniferous forest habitat. This preference may gradually lead to a more open and natural Almindingen Forest, as requested by the Danish Nature Agency Bornholm.